O autorretrato da vida: experiências de sujeitos em sofrimento psíquico - Moya, Maira Kelly Verengue (2010)
This dissertation is based on the researcher's professional experience as a social worker at the Center for Psychosocial Care - CAPS Pindamonhangaba, SP. Aims to research the meanings given by the users enrolled in this service to their experience of life, specifically, to know their life stories and identify how they recognize themselves socially. Assumes that Mental Health has represented a growing field of intervention for the social worker and considers necessary the production of scientific knowledge to enable the theoretical justification of these professionals daily experience. Based on these arguments resides the justification for this research, to the extent it purports to know the views of the users enrolled in this service about their status in society. Has as foundation the concept of Health-Disease Process, understood as the synthesis of the totality of determinations that operate the quality of people's lives. The Psychiatric Reform is the political orientation and the CAPS represent one of the technologies available in the care of the person in psychic distress. It is guided in dialectical and historical materialism as a theoretical framework for understanding and analysis of reality and the researching material. Encourages the use of Oral History as the research methodology once it privileges the social and historical experience of the users: the everyday life, memory and culture. Makes use of the user s narrative recorded during the execution of an intervention project named "Autorretrato da Loucura (Self Portrait of Madness), held in CAPS Pindamonhangaba in 2008. Finally, makes a rough summary of the reality studied